PENGARUH E-SERVICE QUALITY DARI WEBSITE INTERNET BANKING TERHADAP BRAND EQUITY MELALUI VARIABEL MEDIATOR PERCEIVED VALUE DAN CORPORATE CREDIBILITY - Sorta Vera Silitonga (Panorama Nusantara, 2019)
The internet and information techonology become more important not only to provide customers with efficient banking services, but also for banks to win competitive advandage. Technology is utilized in marketing strategy to create and improve the superior service. Banks have begun to set up their own web portals, include banking that has service as a branch. For service industry, especially banks, creating superior quality of service is a strategy to differentiate itself from other service providers. This research is aimed purpose to analize the influence of e-service quality both direct and indirect influence in service of website internet banking. Indirect influence will be mediated by corporate credibility and perceived value. Definition of brand equity refers to consumer-based brand equity. About 257 respondents who have and use website internet banking of BCA, Bank Mandiri and Citibank participate to answer the questioner (email or printed). The primary data will analysed by using Structural Equation Modelling (SEM). Result shows that e-service quality has indirect influence to brand equity. E-service influences significantly brand equity if banks have high corporate credibility and perceived value.